The Virtual Community of Practice Facilitation Model: A Conceptual Framework for Healthcare Professional Education - Kellam, Hugh; Cook, Clare; Smith, Deborah L; Haight, Pam (International journal of technology and human interaction, 2023)
This study examines the instructional design, learning experiences, and outcomes of a virtual community of practice (VCoP). In 2019, the Northern Ontario School of Medicine launched a continuing professional development program consisting of an asynchronous online module followed by an optional series of facilitated case-based videoconference workshops, designed as a VCoP. This program evaluation study employed a convergent parallel mixed methods design and combined data sources from participant pre- and post-program surveys and reflections with a content analysis of semi-structured interviews. The paper reports key enablers that contributed to the following outcomes: the value of an online module as a baseline of knowledge; the impact of the shared case studies, experiences, and peer support on reflection and modifications to medical practice; and skill development and patient-centered care as a result of module and VCoP participation. A model for the effective design and delivery of VcoPs is proposed that results in acquisition of new knowledge and skills and promotes patient-centred practice.